Technology Strategy in Product Development for Sustainable Innovation in Global Markets - Mardikaningsih, Rahayu; Hariani, Mila (Journal of Social Science Studies, 2023)
In an era of increasingly fierce global competition, companies need to develop innovative products to remain competitive in the market. One way to achieve this is by integrating technology in the product development process. The use of technology, such as engineering software, management information systems, and other information technologies, enables companies to accelerate product development cycles, increase quality, and create more efficient products. The success of product development depends not only on the application of the technology itself, but also on the alignment between the technology and the company's long-term goals. For this reason, companies need to ensure that the strategies used can support sustainability and continuous innovation. This also engages good management and upskilling of the workforce who are able to adapt to the latest technology. This research examines various approaches in utilizing technology for product innovation and how companies can adapt to rapid market changes. By paying attention to these factors, companies can be better prepared to face global challenges, produce innovative products, and achieve sustainable competitive advantage.